The effects of ring substituents in aniline on the reactivity of PANI with hydrogen tetrachloroaurate and the dispersion of gold nanoparticles. (5th November 2015) - Kabomo, T. M.; Scurrell, M. S.
Abstract : As expected from theoretical predictions, the polymerization of aniline was affected by the substituent group on the benzene ring. The rate of the polymerization varied as poly(2‐chloroaniline) (PANICl) < < poly(2‐methylaniline) (PANIMe) < polyaniline (PANI). While the rate of polymerization was determined largely by electronic effects of the substituent groups, the reactivity of the polymers was determined by the steric effects. The order of the rate of reaction of the polymers with AuCl4 − was PANIMe < PANICl < < PANI. The amount of Au incorporated into the polymer matrix followed a similar trend. However, the size of the gold nanoparticles did not differ greatly. Gold nanoparticles dispersed on PANICl and PANIMe were more stable in acidic media than those on PANI. Copyright © 2015 John Wiley & Sons, Ltd.